Incidence, mechanism and outcomes of schisis retinal detachments revealed through a prospective population-based study. Issue 8 (5th January 2017) - Xue, Kanmin; Muqit, Mahiul M K; Ezra, Eric; Charles, Stephen J; Yorston, David; Mitra, Arijit; Patel, Chetan K
Abstract : Aim: To determine the incidence, presentation and outcomes of progressive sight-threatening retinal detachment (RD) complicating degenerative retinoschisis. Methods: We conducted the first prospective population-based epidemiological study of progressive schisis detachment over a 1-year period (2014–2015) in the UK. Case ascertainment was via monthly British Ophthalmological Surveillance Unit reporting cards sent to all ophthalmologists in the UK. For each reported case, data were collected using incident and 6 months follow-up questionnaires gathering information including demographic, presenting symptoms, retinal findings, primary management, primary outcome, secondary management and secondary outcome. Results: Fifty-five cases of progressive schisis RD were identified with similar age distribution to conventional rhegmatogenous RD (mean age 64.0 years, range 20–88), and male-to-female ratio of 2.3:1. The locations of schisis detachments were predominantly supratemporal (46.7%) and infratemporal (35.6%). At least 70% of schisis RD were associated with posterior vitreous detachment (PVD) at presentation and 21% with grade B-C proliferative vitreoretinopathy. Primary management consisted of pars plana vitrectomy (82%), scleral buckle (9%), observation (4%), laser (2%) and combined vitrectomy-buckle (2%). Primary reattachment rate was 70%. Final reattachment rate was 87% with mean best-corrected visual acuity of 0.49 Decimal (SD 0.34) for fovea-on and 0.42 Decimal (SD 0.29) for fovea-off schisis detachments at mean follow-up of 8.7 months (SE 1.0). Conclusions: The estimated annual incidence of progressive schisis RD was 0.85 per million population (95% CI 0.64 to 1.11), equivalent to around 0.66% of all rhegmatogenous RD. PVD may play a key pathogenic role in the development of progressive schisis detachments. Surgical outcomes are inferior to those of conventional rhegmatogenous RD.